Pro- and anti-inflammatory biomarkers and traumatic brain injury outcomes: A review. (October 2018) - Rodney, Tamar; Osier, Nicole; Gill, Jessica
Highlights: Pro- and anti-inflammatory proteins may play important roles after brain injury. Increased IL6, IL1, IL8, IL10 and TNFα levels are associated with worse outcomes. Most studies focused on mortality and morbidity outcomes. Most studies focused on severe TBI outcomes. Abstract: Traumatic Brain Injury (TBI) triggers a cascade of secondary biological and physiological effects that are variable, depending on the severity, location, and complexity of the injury. Improved diagnosis and prognosis of brain injury may be possible by examining changes in protein biomarker concentrations and, determining their role in long-term outcomes may improve treatment. One promising direction for biomarker research surrounds pro- and anti-inflammatory cytokines which may have utility for predicting short and long-term prognosis after TBI, and may also be therapeutic targets in shaping neuronal recovery following a TBI. The purpose of this review is to examine the relationship between TBI symptoms and changes in pro- and anti- inflammatory biomarkers. Eighteen (18) published articles met criteria for inclusion. Fourteen studies focused on individuals with severe TBI. Increased levels of interleukin (IL)-6, IL-1, IL-8, IL-10 and tumor necrosis factor alpha (TNFα) were associated with worse outcomes, with most studies focusing on morbidity and mortality. It is important to identify the biochemical changes that may influence or initiate the presentation of health outcomes after a TBI. Earlier identification of symptoms associated with these biochemical changes can be used to support better treatment planning, targeted interventions and ultimately, improvement in patient outcomes.